Consumo e digestibilidade aparente do feno de Andropogon gayanus colhido em três diferentes idades - Andre Cayo Cavalcanti (2010)
The study it was designed to compare the voluntary consumption and apparent digestibility of dry matter, crude protein, fiber fractions, energy and nitrogen balance of Andropogon gayanus hays at three different stages. That hay was harvested at 56, 84 and 112 days. The voluntary intake and apparent digestibility of the hays were determined by using 18 (eighteen) sheep in metabolic cages. Each was statistically analyzed on a random delimitation, with tree treatment and six repetitions. There were statistical differences (P<0,05) between voluntary intake of dry matter, organic matter, neutral detergent fiber, acid detergent fiber, lignin and energy in g/UTM/day between three different stages. The apparent digestibility of dry matter, organic matter, fiber fractions and energy was superior (P<0,05) for hays in stages 56, 84 days with relation or stage 112 days. The apparent digestibility crude protein in Andropogon gayanus hays in stage the 56 days was superior (P<0,05) us stages 84 and 112 days. The consumption or crude protein and crude protein in g/UTM/day in Andropogon gayanus hays or stage at 56 days beside was view superior (P<0,05) in relation or stages 84 and 112 days. The 56, 84 days was efficient in increasing the intake and the digestibility in Andropogon gayanus hays.